Energy- and material-efficient Ti-6Al-4V sheet part fabrication by the novel TISTRAQ-process, including resistance heating and tool-based quenching: Insights into test stand design and material potential - Pfeffer, Nina; Kaiser, Maximilian Alexander; Feix, Werner; Kälble, Nils; Merten, Mathias; Stark, Andreas; Haufe, Andre; Meyer, Thomas; Tröster, Thomas; Höppel, Heinz Werner (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2025)
Sustainable and lightweight manufacturing processes are essential for reducing greenhouse gas emissions and conserving resources. The novel TISTRAQ-process combines a two-stage, short-time heat treatment with an advanced heating and non-isothermal hot forming strategy, thereby ensuring high material and energy efficiency. In this work, a simplified laboratory-scale test stand was developed, enabling direct electric resistance heating and subsequent tool-based quenching of Ti-6Al-4V sheet strips under near-process conditions, but without the complexity of simultaneous forming. The setup allows systematic variation of key process parameters with minimal material consumption, an approach applied in this study to investigate their influence on material properties. Finite element simulations supported the test stand design and provided a valuable understanding of temperature inhomogeneities and their relevance for microstructural evolution and process control. The paper provides detailed insights into (i) the design and capabilities of the test stand, (ii) simulation-based evaluation of temperature homogeneity, (iii) the TISTRAQ process route - including resistance heating, tool-based quenching, and additional short-time annealing, (iv) the resulting microstructural and mechanical properties, and (v) the material response to critical parameters. Experimental results confirm the high potential of the TISTRAQ-process to enhance the tensile strength of Ti-6Al-4V. The solution heat treatment temperature and time delay prior to quenching were identified as critical parameters due to their strong influence on microstructure and mechanical behavior. Overall, the study demonstrates how tailored process control can unlock the material potential of Ti-6Al-4V. It also indicates a good scalability of the TISTRAQ-process for lightweight, resource-efficient production of next-generation titanium alloy sheet parts.
CRIS-Team Scopus Importer:2025-09-12
Keywords: Annealing; Energy-efficiency; Martensite; Material-efficiency; Microstructures; Non-isothermal hot forming; Resistance heating; Strengthening; Test stand design; Ti-6Al-4V; TISTRAQ-Process; Tool-based quenching